The Concordance of Recursive Partitioning Analysis (RPA) Class Stratification with Survival of Brain Metastases Patients in Mohammad Hoesin Hospital, Palembang, Indonesia: The concordance of RPA, Diansari et al - Yunni Diansari; Selly Marisdina; Afriani; Dya Anggraeni; Hediaty Syafiera (HM Publisher, 2021)
A B S T R A C TIntroduction: Recursive Partitioning Analysis is one of prognostic scores, has beenvalidated to any different setting. Objective: To identify the concordance of RecursivePartitioning Analysis stratification in survival with brain metastases patients.Methods: Retrospective study was performed on brain metastases patients fromJanuary 2017 until Desember 2019 based on medical record. The follow up timestarted from the first diagnosis of brain metastases to death or last follow up. TheKaplan Meier was used to plot survival curves and the log-rank test was used toanalyse differences between groups Results: Mean overall survival time was 4,67months with 1,14 months for median survival for all patients. According to scoring,mostly (80,8%) patients were in group 3. The median survival time was 7 monthsand 2 months for group 2 and 3. Conclusion: It has shown relatively congruitysurvival in BM patients with stratification of Recursive Partitioning Analysis in ourinstitution.